An optimal control approach to the irrigation planning problem - Lopes, Sofia Oliveira (2013)
We study the irrigation systems as an optimal control problem, where the trajectory is the water in the soil and the control is the amount of water introduced in the soil via irrigation. We consider two problems: rst what we call the Yearly planning problem to determine the amount of water spent along the year and then the Initial planning problem to calculate the minimum amount of water in order to ful ll the culture needs given an initial amount of water at the beginning of a year. Since none of these models are exact representations of reality, especially when uncertainty, like weather, is involved, predictive control techniques are used to replan our problem.